Effect of residual reagents on chalcopyrite losses at Mount Isa Mines copper operation: Part I – evaluation of mineral recoveries. (July 2022) - Forbes, Elizaveta; Britoe Abreu, Susana; Tungpalan, Kate; Sashigunan, Ramya; Runge, Kym; O'Donnell, Roxanne
Graphical abstract: Research highlights: Part I of this works has demonstrated that decontaminating Mt Isa Mines process water improves chalcopyrite losses by circa 66%. The loss reduction could be partially attributed to the degrease in the degree of chalcopyrite entrainment in the flotation system. The reduction in losses can be further partially attributed to the removal of residual collector reagents from chalcopyrite surfaces. Both above mechanisms will be explored in more detail in Part II. Abstract: Mount Isa Mines Copper Operation (MICO), owned by Glencore, is one of the largest copper producers in Australia. The concentrator has a complex circuit, which includes a pre-flotation section designed for early removal of deleterious talc, and other naturally floating gangue including carbonaceous material. The downside of early talc removal is the loss of chalcopyrite to the pre-flotation concentrate. This work investigates the role of residual collector and frother reagents on chalcopyrite losses in the MIM pre-flotation circuit, and the possibility of improving talc recovery whilst keeping chalcopyrite loss to a minimum. In Part I, the flotation response is evaluated as a function of mineral recoveries in order to differentiate talc flotation responses from those of other Methylglyoxal (MgO) containing minerals such as dolomite. This is achieved through the estimation of ore mineral content from elemental assays and a conversion methodology developed from historical mineralogy data.